AN OVERVIEW OF COMPONENTS AND OUTPUTS OF LIVESTOCK RESEARCH IN TAMIL NADU - G. Senthil Kumar; M. Prabu; K.N. Selvakumar; G. Kathiravan; P. Thilakar (Indian Journal of Veterinary and Animal Sciences Research, 2025)
An attempt was made to overview the conduct, components and output of various livestock research activities conducted in TANUVAS for the period from 2008 to 2018. Among 152 projects completed during the study period, there were 52 health projects, 36 production, 25 social science, 16 clinical science, 14 infrastructure, six processing, two environment and one education related projects. The research investment of projects completed from 2008 to 2018 was found to be the highest for Health (Rs.1767.70 lakhs), followed by Infrastructure (Rs.1723.40 lakhs), Production (Rs.668.72 lakhs), Social science (Rs.393.82 lakhs), Clinical science (Rs.360.28 lakhs), Education (Rs.221.47 lakhs), Processing (Rs.87.50 lakhs) and Environment (Rs.14.64 lakhs). Among various livestock species, Poultry research occupied predominant position with 39 numbers of projects with outlay of Rs.791.25 lakhs. It should be noted that the research on companion animals and fodder were less than 10 in last ten years. A total of 44 patents were filed in TANUVAS during last decade, among which seven were granted. It is concluded that the focus should also be made on fodder, swine and companion animal and fodder research.